The use of the results of multiplex analysis of the morphological substrate of the tumor in the differential diagnosis of pigmented and non-pigmented superficial melanomas of the skin using the example of two clinical observations - A. V. Borisov; I. A. Chernov; V. E. Rodionov; A. M. Avdalyan; D. N. Protsenko; A. I. Nichiporov; V. I. Kukushkin; Yu. A. Kirillov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2024)
Observations of pigmented (melanoblastic) and non-pigmented (achromatic) superficial melanomas of the skin are described, for the differential diagnosis of which, along with traditional histological examination, precision (immunohistochemical, molecular genetic) methods of studying the morphological substrate of the tumor were used. Based on the results of Raman spectroscopy of samples of both tumors, their multiplex analysis was carried out, with the help of which a significant number of molecules of various analytes were simultaneously identified in one individual sample of a biological object.